Physical advantages of particles: protons and light ions - Jäkel, Oliver (BJR case reports, 2020)
Proton and ion beam therapy has been introduced in the Lawrence Berkeley National Laboratory in the mid-1950s, when protons and helium ions have been used for the first time to treat patients. Starting in 1972, the scientists at Berkeley also were the first to use heavier ions (carbon, oxygen, neon, silicon and argon ions). The first clinical ion beam facility opened in 1994 in Japan and since then, the interest in radiotherapy with light ion beams has been increasing slowly but steadily, with 13 centers in clinical operation in 2019. All these centers are using carbon ions for clinical application. The article outlines the differences in physical properties of various light ions as compared to protons in view of the application in radiotherapy. These include the energy loss and depth dose properties, multiple scattering, range straggling and nuclear fragmentation. In addition, the paper discusses differences arising from energy loss and linear energy transfer with respect to their biological effects. Moreover, the paper reviews briefly the existing clinical data comparing protons and ions and outlines the future perspectives for the clinical use of ions like oxygen and helium.
Published online: September 26, 2019
Gesehen am 13.05.2020